Faktor-faktor yang mempengaruhi Kinerja Auditor: Profesionalisme, Kompetensi Auditor dan Independensi Auditor - Junisa, Karennia (Balance: Media Informasi Akuntansi dan Keuangan, 2024)
Good audit performance will enable the accounting firm to achieve its objectives and meet the financial reporting needs of stakeholders. Auditors must be skilled to maintain the trust of clients and other users of the audit financial statements. Auditor training improves the auditor's ability to carry out his work during the audit process.The central questions of this article are: (1) Whether auditor ability, auditor professionalism, and auditor independence have an impact on performance. (2) Further review of previous articles, which are still found to be inconsistent. The hope is that this research will contribute new thoughts to the development of audit theory by reviewing aspects of auditor independence, professionalism, and competence in the context of their performance.The purpose of writing this article is to establish hypotheses of influence between variables in further research.The findings of this literature review article are: 1) Auditor competence affects auditor performance; 2) Professionalism has an effect on auditor performance; 3) Auditor independence has an effect on auditor performance.